Bony Metaplasia associated with the delay in the ulcer healing in diabetic patient . A case study - Beatriz Guitton Oliveira; Eliane Pedra Dias; Juliana de Oliveira Araújo; Pricila Rodrigues Leonor; Mariana Morgado Ribeiro (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
This search aims to describe the bony metaplasia found in the histopathological analysis of ulcer in patients observed at the Wound Repair Aid Center at the university hospital. The study is part of a search project applied in CNPq entitled "Delay in the cutaneous ulcers healing: clinical and morphological sectional evaluation", being that during the blades analysis we found out cells that performed different from the osteoblasts. It is about a study of case of a diabetes and chronic renal patient with bad piercing planting. The data collect was based on the instrument of search with clinical and descriptive identification data about the hurt, besides the material for the pathological study histopathological. The morphological result indicates the difference of mesenchymals cells in osteoblasts in the injury, instead of fibroblasts. It can be concluded that the chronicity in the wound made one type of cell to be replaced by another type impairing the scarring